Revision of the Micronoctuidae species occurring in the Russian Far East and neighbouring countries with description of a new species (Lepidoptera, Noctuoidea) - Fibiger, Michael; Kononenko, Vladimir S. (Zootaxa, 2008)
The family Micronoctuidae and the genus Micronoctua Fibiger, 1997 are reported from the Russian Far East and neighbouring countries for the first time. The family is represented in the region by two species in the genera Mimachrostia Sugi, 1982 and Micronoctua both occurring in Russian Far East, Korea, China and Japan. The northern distribution limit of the family Micronoctuidae is the middle of the Amur River (50°31΄N, 137°035΄E), reached by Mimachrostia fasciata Sugi, 1982. The new species, Micronoctua occi, sp. n. is described from Russian Far East, the Korean peninsula, China and the Tsushima Islands of Japan. The male and female genitalia are illustrated and compared with those of Micronoctua karsholti. Distribution maps for the two species are presented.